PROBLEMS OF NATIONAL IDENTITY AND PROFESSIONAL DEVELOPMENT IN THE CONTEXT OF GLOBALIZATION - Kobilov Uchkun Ulmasovich (Modern American Journals, 2025)
In the twenty-first century, globalization has emerged as a transformative force reshaping cultures, economies, and social institutions worldwide. While globalization has accelerated professional development by creating opportunities for knowledge exchange, technological advancement, and labor mobility, it has also intensified concerns over the erosion of national identity. National identity, as a collective sense of belonging, faces challenges from cultural homogenization, dominance of global languages, and shifts in traditional values. This article explores the tension between preserving national identity and achieving professional growth in a globalized context. It emphasizes the importance of balancing openness to global influences with safeguarding cultural uniqueness. The analysis considers education, migration, and technological change as central factors influencing identity and professional development. Ultimately, the article argues for integrative policies that allow individuals and societies to benefit from globalization while maintaining their national identity.
Keywords: National identity, globalization, professional development, cultural homogenization, migration, education, technological change